2021
DOI: 10.1021/acsami.1c01329
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Robustness of Metal–Organic Frameworks for Synthetic Chemistry

Abstract: Metal–organic frameworks (MOFs) are emerging as sustainable reagents and catalysts with promising applications in synthetic chemistry. Although the hydrothermal stabilities of MOFs have been well studied, their robustness toward various reagents, including acids, bases, nucleophiles, electrophiles, oxidants, and reductants, remains poorly characterized. As such, heterogeneous platforms for promising catalysts are generally identified on an ad hoc basis and have largely been limited to carboxylate frameworks to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 70 publications
0
61
0
Order By: Relevance
“…4,[7][8][9][10][11][12] Despite challenges in MOF synthesis [13][14] and post-synthetic modification 15 , intense synthesis effort has led to rapid growth 16 in the number of reports of experimentally realized MOFs. MOFs with varying pore size, metals, and linker chemistry have demonstrated desirable properties for storage [17][18] , separations 7,19 , sensing [20][21] , conductivity [22][23][24] , and catalysis [25][26][27][28][29] . Most MOFs are formed with solvent present in their pores that must be removed for such applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,[7][8][9][10][11][12] Despite challenges in MOF synthesis [13][14] and post-synthetic modification 15 , intense synthesis effort has led to rapid growth 16 in the number of reports of experimentally realized MOFs. MOFs with varying pore size, metals, and linker chemistry have demonstrated desirable properties for storage [17][18] , separations 7,19 , sensing [20][21] , conductivity [22][23][24] , and catalysis [25][26][27][28][29] . Most MOFs are formed with solvent present in their pores that must be removed for such applications.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) have the potential to revolutionize catalysis and functional materials design due to their reticular nature and well-defined, isolated metal sites. , To meet numerous design criteria, an exhaustive search of MOFs must be carried out for each potential application, beyond the tens of MOFs that an experimentalist could synthesize. The modularity of inorganic secondary building units (SBUs) and linkers that are the building blocks of MOFs have motivated the search for new materials via virtual high throughput screening (VHTS). , Despite challenges in MOF synthesis , and postsynthetic modification, intense synthesis effort has led to rapid growth in the number of reports of experimentally realized MOFs. MOFs with varying pore size, metals, and linker chemistry have demonstrated desirable properties for storage, , separations, , sensing, , conductivity, and catalysis. Most MOFs are formed with solvent present in their pores that must be removed for such applications. Although new methods for solvent removal have been developed to activate these materials, , many crystalline MOFs collapse upon activation, ,, rendering them unusable …”
Section: Introductionmentioning
confidence: 99%
“…35,36 In contrast to the wide study of amine-functionalized porous solids for CO2 capture, hydroxide-and alkoxide-functionalized porous solids remain remarkably understudied. 32 This may be due in part to the generally poor stability of traditional solid supports such as mesoporous silicas 37 and MOFs 38,39 towards OH − . Nonetheless, previous studies have shown that robust azolate MOFs bearing terminal M−OH (M = Zn, Ni, Co) sites can undergo selective and reversible reaction with CO2 to form metal-bound bicarbonates, akin to the enzyme carbonic anhydrase.…”
Section: Introductionmentioning
confidence: 99%
“…After nearly two decades since the first report of Cr-MOF, there are still few Cr-MOFs. Furthermore, known low-connected Cr-MOFs have limited stability, especially in basic solution (stable only at pH ≤ 12). ,, …”
mentioning
confidence: 99%
“…Furthermore, known low-connected Cr-MOFs have limited stability, especially in basic solution (stable only at pH ≤ 12). 29,31,32 To make new Cr-MOFs with superior stability, going beyond currently known 6-connected Cr 3 O frameworks is a worthy pursuit. High-connected Cr-MOFs are expected to be difficult to crystallize, given what we know about lowconnected Cr-MOFs.…”
mentioning
confidence: 99%